2008
DOI: 10.4049/jimmunol.181.2.1170
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 Receptor 1 Expression on Dendritic Cells Is Required for the Development of Th2 Responses and Allergen-Induced Airway Hyperresponsiveness

Abstract: Dendritic cells (DC) are important APCs that control allergen-induced airway responses by interacting directly with T cells. Leukotriene B4 (LTB4), interacting with its high-affinity receptor, LTB4 receptor 1 (BLT1), is known to attract and activate leukocytes during inflammation. We have previously shown that BLT1 expression on Ag-primed T cells is required for the development of airway hyperresponsiveness (AHR; Miyahara et al. 2005. Am. J. Respir. Crit. Care Med. 172: 161–167). However, the role for the LTB4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
58
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 45 publications
4
58
1
Order By: Relevance
“…aGalCer BMDCs also demonstrated significant increases in levels of IFN-g in PBLNs, where allergen-captured DCs migrate and present Ag to recirculating naive CD4 + and CD8 + cells (7,10,11). In the lungs of recipients of OVA/aGalCer BMDCs, the number of iNKT cells that produced IFN-g was significantly increased compared with the numbers in recipients of OVA BMDCs.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…aGalCer BMDCs also demonstrated significant increases in levels of IFN-g in PBLNs, where allergen-captured DCs migrate and present Ag to recirculating naive CD4 + and CD8 + cells (7,10,11). In the lungs of recipients of OVA/aGalCer BMDCs, the number of iNKT cells that produced IFN-g was significantly increased compared with the numbers in recipients of OVA BMDCs.…”
Section: Discussionmentioning
confidence: 83%
“…Because DCs are important APCs in the lung and play a critical role in the induction or the initiation phase of allergic airway inflammation and AHR (7,8), we sought to define whether this ligand for iNKT cells could modify DC function and, in turn, iNKT cell function. To focus on the initiation phase, we showed that transfer of OVA BMDCs intratracheally could initiate the development of AHR and airway inflammation in response to OVA challenge in the absence of prior sensitization with adjuvant (10,11). In this way, allergen-pulsed BMDCs that are exposed to a ligand for iNKT cells may be used to determine the potential role for iNKT cells in the initiation phase, prior to allergen challenge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LTB 4 exerts a diverse range of effects on the function of these latter immune cells (2) and also the activity of eosinophils, basophils, and lymphocytes (3)(4)(5)(6)(7)(8). Most, if not all, of these immune functions are associated with the BLT1 receptor, with BLT2 generally more associated with cancer progression (9).…”
mentioning
confidence: 99%